Visualization of rainfall data distribution using quintic triangular Bezier patches - Saaban, Azizan; Abd Majid, Ahmad; Mt Piah, Abd Rahni (Universiti Sains Malaysia, 2008)
This paper discusses the use of a C2 interpolant which is positive everywhere and the need to preserve positivity in the case of visualization of rainfall data distribution of Peninsular Malaysia. The results from our previous work, where sufficient conditions on Bezier points have been derived, will be used in order to ensure that surfaces comprising quintic Bezier triangular patches are always positive. The first and second derivatives at the data sites are calculated and modified (if necessary) to ensure that these conditions are satisfied. A number of examples are presented based on the average monthly rainfall data in a particular year at various locations in Peninsular Malaysia.